2005
DOI: 10.1038/sj.cr.7290341
|View full text |Cite
|
Sign up to set email alerts
|

Long-term modifications of blood pressure in normotensive and spontaneously hypertensive rats by gene delivery of rAAV-mediated cytochrome P450 arachidonic acid hydroxylase

Abstract: Arachidonic acid cytochrome P-450 (CYP) hydroxylase 4A isoforms, including 4A1, 4A2, 4A3 and 4A8 in the rat kidney, catalyze arachidonic acid to produce 19/20-Hydroxyeicosatetraenoic acids (20-HETE), a biologically active metabolite, which plays an important role in the regulation of blood pressure. However, controversial results have been reported regarding the exact role of 20-HETE on blood pressure. In the present study, we used recombinant adenoassociated viral vector (rAAV) to deliver CYP 4A1 cDNA and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…In the present study, animals were pretreated with HET0016 for 5 min before MCAO to determine the contribution of 20-HETE to ischemic stroke outcomes in normotensive and hypertensive rats. Administration of HET0016 also reduced MAP in SHR and SHRSP by about 30 mmHg, which is consistent with previous suggestions that elevated vascular production of 20-HETE may contribute to increased peripheral vascular tone and the maintenance of hypertension in the SHR (17,30,52,63,64,67). This reduction in MAP in SHR and SHRSP may also contribute to the reduction in infarct size with HET0016 treatment by reducing the driving force for edema formation.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, animals were pretreated with HET0016 for 5 min before MCAO to determine the contribution of 20-HETE to ischemic stroke outcomes in normotensive and hypertensive rats. Administration of HET0016 also reduced MAP in SHR and SHRSP by about 30 mmHg, which is consistent with previous suggestions that elevated vascular production of 20-HETE may contribute to increased peripheral vascular tone and the maintenance of hypertension in the SHR (17,30,52,63,64,67). This reduction in MAP in SHR and SHRSP may also contribute to the reduction in infarct size with HET0016 treatment by reducing the driving force for edema formation.…”
Section: Discussionsupporting
confidence: 78%
“…7 The delivery of CYP4A1 cDNA increased BP in Sprague-Dawley rat, whereas transferring antisense CYP4A1 cDNA into SHR decreased BP. 20 Our findings that Hap I of CYP4F2 regulatory region was associated with elevated urinary 20-HETE levels as well as increased risk for hypertension supported a prohypertensive effect of renal 20-HETE and CYP4F2 expression; however, Gainer et al 9 reported that a functional variant of CYP4A11 with reduced 20-HETE synthase activity was associated with hypertension, suggesting an antihypertensive action of 20-HETE. In vivo investigations of the synergistic or antagonistic effect of functional polymorphisms as well as haplotypes in the CYP4F2 and CYP4A11 genes would be the focus of further studies.…”
Section: Discussioncontrasting
confidence: 42%
“…In this study, we applied an rAAV vector to deliver SLC directly into the tumor cells. This choice was based on the broad host range, excellent safety profile, and the ability of rAAV to integrate into the host genome as well as to provide long-term expression in infected hosts (20,52,57). Although studies have addressed the efficacy of AAV-mediated gene therapy in different human and mammalian cell types, the most efficient vector transduction in vivo has been reported in skeletal muscle and brain, followed by hepatocytes (4,22,29,52,58).…”
Section: Discussionmentioning
confidence: 99%